Antibacterial anti-aging ABS (acrylonitrile butadiene styrene) material as well as preparation method and application thereof
By using hydrogenated copolymer rubber as a graft toughening modifier and directly introducing antibacterial agents in ABS materials, the problems of poor anti-aging performance and insufficient antibacterial performance of ABS materials are solved, and both anti-aging and antibacterial performance are achieved, which significantly improves the use performance of the material.
Patent Information
- Application Number
- CN202411952881.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing ABS materials have poor anti-aging performance, poor long-term use performance and insufficient antibacterial performance.
Hydrogenated copolymer rubber is used as graft toughening modifier to prepare anti-aging ABS through free radical polymerization, and antibacterial agent is directly introduced into the ABS substrate to form in situ antibacterial ABS. At the same time, anti-photoaging agent, flame retardant, toughening agent, filler additive and other components are added to prepare ABS materials with both anti-aging and antibacterial properties through the process of composite materials.
It significantly improves the anti-aging performance and antibacterial properties of ABS materials. Compared with conventional technologies, the anti-aging performance is 30%, and it also has excellent mechanical properties and good technical effects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS materials, and in particular to an antibacterial and aging-resistant ABS material and a preparation method and application thereof. Background Art
[0002] ABS resin (acrylonitrile / butadiene / styrene terpolymer) is prepared by heat initiation or initiator initiation, bulk method, emulsion method, etc. It has certain toughness, glossiness, processing fluidity, easy coloring and other characteristics. It is a plastic variety with relatively excellent comprehensive performance and is widely used in electronics, electrical appliances, instruments, building materials, auto parts and office equipment, etc. Since the double bonds contained in the butadiene component in ABS are easily oxidized and degraded under the action of ultraviolet rays, resulting in poor weather resistance, it is of great significance to effectively solve the anti-aging performance of ABS.
[0003] In addition, in the fields of household appliances, medical treatment and health, the requirements for the antibacterial properties of material products are getting higher and higher. Chinese patents CN114702780 and CN114133691 respectively use silver ions, nano zinc oxide, nano copper oxide or zinc ions to prepare antibacterial ABS materials. Chinese patent CN115418071 discloses a silver-loaded aluminosilicate to improve the antibacterial properties of ABS, solving the problem that conventional silver ion antibacterial agents are prone to discoloration. Chinese patents CN114163575 and CN117616057 have developed antibacterial ABS resins from the perspective of comonomers. Developing an ABS that is anti-aging, has excellent performance and has antibacterial properties has always been an important topic. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the ABS in the prior art has poor anti-aging performance, poor long-term use performance and insufficient antibacterial performance, and provides an antibacterial and anti-aging ABS material having both excellent anti-aging performance and antibacterial performance.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: an antibacterial and aging-resistant ABS material, comprising an ABS substrate, and based on 100 parts by weight of the ABS substrate, further comprising the following components: (i) 1 to 10 parts of anti-photoaging agent; (ii) 1 to 10 parts of an antimicrobial agent; (iii) 1 to 5 parts of toughening agent; (iv) 10 to 20 parts of flame retardant; (v) 5-35 parts of filling additives; (vi) 0-2 parts of plasticizer; (vii) 0-2 parts of antioxidant; The ABS substrate is prepared by free radical polymerization reaction under the action of an initiator, with aromatic vinyl, nitrile vinyl and acrylate as copolymer monomers, and at least one of hydrogenated butadiene / styrene copolymer rubber, hydrogenated styrene / isoprene copolymer rubber and hydrogenated butadiene / styrene / isoprene copolymer rubber as a graft toughening modifier; Wherein, the aromatic vinyl is selected from at least one of styrene, methyl styrene, C1-C6 hydrocarbon-substituted styrene, and C1-C6 hydrocarbon-substituted methyl styrene; The nitrile-based ethylene is selected from at least one of acrylonitrile and methacrylonitrile; The acrylic acid ester is selected from at least one of C1~C6 alkyl acrylic acid ester and C1~C6 alkyl methacrylic acid ester; The molar ratio of the aromatic vinyl, nitrile vinyl and acrylic acid ester is (40-85): (10-40): (5-20); The initiator is selected from at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, di-tert-butyl peroxide, diisopropylbenzene peroxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, and diisobutyl peroxydicarbonate; The molar amount of the initiator is 0.01-1% of the total amount of the comonomer; The number average molecular weight of the graft toughening modifier is 50,000 to 150,000 g / mol, preferably 80,000 to 120,000 g / mol; The degree of hydrogenation of the graft toughening modifier is 50-100%; The weight percentage of the graft toughening modifier is 10-15% of the total ABS; The temperature of the free radical polymerization reaction is 50-150° C., and the reaction time is 2-24 hours.
[0006] In the above technical solution, the melt flow rate of the ABS at 220°C and 5 kg is 8 to 20 g / 10 min, preferably 10 to 18 g / 10 min; The number average molecular weight of the ABS is 100,000 to 200,000 g / mol, preferably 150,000 to 180,000 g / mol.
[0007] In the above technical solution, the anti-light aging agent is selected from at least one of benzotriazole, polyhydroxybenzene, benzophenone, benzoxazinone and their derivatives.
[0008] In the above technical solution, the antibacterial agent is selected from at least one of chitosan, nano-tin oxide and nano-silicon dioxide; The antibacterial agent is added to the free radical polymerization reaction of the ABS substrate to obtain ABS with in-situ antibacterial properties.
[0009] In the above technical solution, the toughening agent is selected from at least one of hydrogenated butadiene / styrene copolymer rubber, hydrogenated styrene / isoprene copolymer rubber, and hydrogenated butadiene / styrene / isoprene copolymer rubber; The number average molecular weight of the toughening agent is 50,000 to 150,000 g / mol, preferably 80,000 to 120,000 g / mol; The degree of hydrogenation of the toughening agent is 50-100%.
[0010] In the above technical solution, the flame retardant is selected from at least one of triphenyl phosphate, triisopropylphenyl phosphate, bisphenol A bis(diphenyl phosphate), bisphenol A bis(diisopropylphenyl phosphate), resorcinol bis(diphenyl phosphate), and resorcinol bis(diisopropylphenyl phosphate); The flame retardant further comprises fluorinated polyolefin; the fluorinated polyolefin is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, and ethylene / tetrafluoroethylene copolymer; The fluorinated polyolefin accounts for 0.1-10% of the total weight of the flame retardant, preferably 2-8%.
[0011] In the above technical solution, the filling auxiliary agent is selected from at least one of talc, mica, wollastonite, glass microspheres, glass fiber, graphite, carbon fiber, and graphene; The plasticizer is selected from at least one of dibutyl phthalate, dioctyl phthalate and diphenyl phthalate; The antioxidant is selected from at least one of hindered phenols, phosphites, thioesters and their derivatives.
[0012] In order to solve the above technical problems, the present invention provides a method for preparing an antibacterial and aging-resistant ABS material, comprising the following steps: ABS, light aging inhibitor, antibacterial agent, toughening agent, flame retardant, filling aid, plasticizer and antioxidant are mixed and then melt-processed and extruded by a twin-screw extruder to obtain the antibacterial and aging-resistant ABS material; The processing temperature is 200-240° C., and the screw speed is 200-800 rpm.
[0013] In order to solve the above technical problems, the present invention provides a use of the antibacterial and aging-resistant ABS material, which is used in but not limited to the fields of medical treatment, sanitation, home appliances, and automobiles.
[0014] Technical advantages of the present invention: (1) Hydrogenated copolymer rubber is used as a graft toughening modifier to directly prepare anti-aging ABS through free radical polymerization reaction. Compared with the conventional polybutadiene graft toughening modifier, the anti-aging performance is improved by 30%. At the same time, some hydrogenated copolymer rubber is added as a toughening agent to the blending system of ABS / antibacterial agent / flame retardant / filling agent, which gives the ABS material excellent mechanical properties from the interface phase and the matrix phase.
[0015] (2) In-situ antibacterial ABS is formed by directly introducing the antibacterial agent into the free radical polymerization reaction of the ABS substrate.
[0016] (3) By compounding anti-aging ABS with antibacterial agents, flame retardants, toughening agents, filling additives, etc., an ABS material with both anti-aging and antibacterial properties was obtained, achieving good technical results.
[0017] The following analytical methods were used to evaluate the physicochemical properties of the materials: Notched impact strength test: measured according to ASTM D256 standard.
[0018] Oxygen index test: measured according to ISO 4589-2 standard.
[0019] Antibacterial performance test: Determined according to GB / T 31402 standard.
[0020] Aging resistance test: Aging under 260nm ultraviolet light and 55℃, and testing impact strength.
[0021] The present invention will be further described below by way of examples. DETAILED DESCRIPTION
[0022] [Example 1] 104 kg of styrene, 9.94 kg of acrylonitrile, 8.875 kg of tert-butyl methacrylate were added to the reactor, and then 12.3 kg of hydrogenated butadiene / styrene copolymer rubber (molar ratio 70 / 30, hydrogenation degree 85%, number average molecular weight 105,000 g / mol) was added and stirred until completely dissolved; 250 g of diisopropylbenzene peroxide was added and polymerized at a reaction temperature of 90°C for 10 hours to obtain ABS substrate-1 with a number average molecular weight of 170,000 g / mol and a melt flow rate of 15 g / 10 min at 220°C / 5 kg.
[0023] [Example 2] 104 kg of styrene, 3.313 kg of acrylonitrile, 26.625 kg of tert-butyl methacrylate were added to the reactor, and then 13.4 kg of hydrogenated butadiene / styrene copolymer rubber (molar ratio 70 / 30, hydrogenation degree 85%, number average molecular weight 105,000 g / mol) was added and stirred until completely dissolved; 170 g of diisopropylbenzene peroxide was added and polymerized at a reaction temperature of 90°C for 10 hours to obtain ABS substrate-2 with a number average molecular weight of 180,000 g / mol and a melt flow rate of 20 g / 10 min at 220°C / 5 kg.
[0024] [Example 3] 104 kg of styrene, 26.5 kg of acrylonitrile, 14.33 kg of methyl acrylate were added to the reactor, followed by 21.7 kg of hydrogenated butadiene / styrene / isoprene copolymer rubber (molar ratio 50 / 30 / 20, degree of hydrogenation 60%, number average molecular weight 81,000 g / mol) and 1.5 kg of chitosan, and stirred until completely dissolved; 360 g of tert-butyl peroxide 2-ethylhexanoate was added, and polymerized at a reaction temperature of 115°C for 16 hours to obtain ABS substrate-3 with a number average molecular weight of 130,000 g / mol and a melt flow rate of 11.5 g / 10 min at 220°C / 5 kg.
[0025] [Example 4] 5000 g of ABS substrate-1, 100 g of benzophenone, 300 g of nano-tin oxide, 250 g of hydrogenated butadiene / styrene copolymer rubber (molar ratio 70 / 30, hydrogenation degree 85%, number average molecular weight 105,000 g / mol), 800 g of triphenyl phosphate, 40 g of ethylene / tetrafluoroethylene copolymer (molar ratio 50 / 50), 1000 g of mica, 25 g of dibutyl phthalate, and 40 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester were blended, and then melt-processed by a twin-screw extruder at a temperature of 225°C and a screw speed of 500 rpm to obtain an antibacterial and aging-resistant ABS material. The performance test results are shown in Table 1.
[0026] [Example 5] 5000 g of ABS substrate-2, 100 g of benzophenone, 300 g of nano-tin oxide, 250 g of hydrogenated butadiene / styrene copolymer rubber (molar ratio 70 / 30, hydrogenation degree 85%, number average molecular weight 105,000 g / mol), 800 g of triphenyl phosphate, 40 g of ethylene / tetrafluoroethylene copolymer (molar ratio 50 / 50), 1000 g of mica, 25 g of dibutyl phthalate, and 40 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester were blended, and then melt-processed by a twin-screw extruder at a temperature of 225°C and a screw speed of 500 rpm to obtain an antibacterial and aging-resistant ABS material. The performance test results are shown in Table 1.
[0027] [Example 6] 3000 g of ABS substrate-1, 2000 g of ABS substrate-2, 100 g of benzophenone, 300 g of nano-tin oxide, 250 g of hydrogenated butadiene / styrene copolymer rubber (molar ratio 70 / 30, hydrogenation degree 85%, number average molecular weight 105,000 g / mol), 800 g of triphenyl phosphate, 40 g of ethylene / tetrafluoroethylene copolymer (molar ratio 50 / 50), 1000 g of mica, 25 g of dibutyl phthalate, and 40 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester were blended, and then melt-processed by a twin-screw extruder at a temperature of 225°C and a screw speed of 500 rpm to obtain an antibacterial and aging-resistant ABS material. The performance test results are shown in Table 1.
[0028] [Example 7] 5000 g of ABS substrate-3, 250 g of benzotriazole, 300 g of nano-silicon oxide, 150 g of hydrogenated butadiene / styrene copolymer rubber (molar ratio 70 / 30, hydrogenation degree 85%, number average molecular weight 105,000 g / mol), 100 g of hydrogenated butadiene / styrene / isoprene copolymer rubber (molar ratio 50 / 30 / 20, hydrogenation degree 60%, number average molecular weight 81,000 g / mol), 1000 g of resorcinol bis(diphenyl phosphate), 15 g of polytetrafluoroethylene, 300 g of graphite, and 30 g of dibutyl phthalate were blended, and then melt-processed by a twin-screw at a temperature of 220°C and a screw speed of 500 rpm, and extruded to obtain an antibacterial and aging-resistant ABS material. The performance test results are shown in Table 1.
[0029] [Comparative Example 1] 5000 g ABS (styrene / butadiene / acrylonitrile molar ratio 70 / 15 / 15), 250 g butadiene / styrene copolymer rubber (molar ratio 70 / 30, number average molecular weight 105,000 g / mol), 800 g triphenyl phosphate, 40 g ethylene / tetrafluoroethylene copolymer (molar ratio 50 / 50), 1000 g mica, 25 g dibutyl phthalate, 40 g 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester were blended, and then melt-processed by a twin-screw extruder at a temperature of 225°C and a screw speed of 500 rpm, and extruded to obtain a modified ABS material. The performance test results are shown in Table 1.
[0030] [Comparative Example 2] 5000 g of ABS (styrene / butadiene / acrylonitrile molar ratio 70 / 15 / 15), 25 g of dibutyl phthalate, and 40 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate were blended, and then melt-processed by a twin-screw extruder at a temperature of 225°C and a screw speed of 500 rpm to obtain a modified ABS material. The performance test results are shown in Table 1.
[0031] Table 1 Examples 4 to 7 use a light aging stabilizer, an antibacterial agent, a hydrogenated binary or ternary copolymer rubber, and a high-efficiency flame retardant in combination with the ABS resin of the special structure prepared by the present invention to construct an ABS material with both anti-aging and antibacterial properties. Compared with the unhydrogenated binary copolymer rubber and the unfunctionalized modified ABS material in Comparative Examples 1 to 2, the light aging resistance is excellent, highlighting the advantages of the technology of the present invention.
Claims
1. An antibacterial and aging-resistant ABS material, characterized in that: The invention comprises an ABS substrate, and based on 100 parts by weight of the ABS substrate, the following components are also included: (i) 1 to 10 parts of anti-photoaging agent; (ii) 1 to 10 parts of an antimicrobial agent; (iii) 1 to 5 parts of toughening agent; (iv) 10 to 20 parts of flame retardant; (v) 5-35 parts of filling additives; (vi) 0-2 parts of plasticizer; (vii) 0-2 parts of antioxidant; The ABS substrate is prepared by free radical polymerization reaction under the action of an initiator, with aromatic vinyl, nitrile vinyl and acrylate as copolymer monomers, and at least one of hydrogenated butadiene / styrene copolymer rubber, hydrogenated styrene / isoprene copolymer rubber and hydrogenated butadiene / styrene / isoprene copolymer rubber as a graft toughening modifier.
2. The antibacterial and aging-resistant ABS material according to claim 1, characterized in that: The aromatic vinyl is selected from at least one of styrene, methyl styrene, C1-C6 hydrocarbon-substituted styrene, and C1-C6 hydrocarbon-substituted methyl styrene; The nitrile-based ethylene is selected from at least one of acrylonitrile and methacrylonitrile; The acrylic acid ester is selected from at least one of C1-C6 alkyl acrylic acid ester and C1-C6 alkyl methacrylic acid ester; The molar ratio of the aromatic vinyl, nitrile vinyl and acrylic acid ester is (40-85): (10-40): (5-20); The initiator is selected from at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, di-tert-butyl peroxide, dicumyl peroxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, and diisobutyl peroxydicarbonate; The molar amount of the initiator is 0.01-1% of the total amount of the comonomer; The number average molecular weight of the graft toughening modifier is 50,000 to 150,000 g / mol; The degree of hydrogenation of the graft toughening modifier is 50-100%; The weight percentage of the graft toughening modifier accounts for 10-15% of the total ABS; The temperature of the free radical polymerization reaction is 50-150° C., and the reaction time is 2-24 hours.
3. The antibacterial and aging-resistant ABS material according to claim 1, characterized in that: The anti-light aging agent is selected from at least one of benzotriazole, polyhydroxybenzene, benzophenone, benzoxazinone and derivatives thereof.
4. The antibacterial and aging-resistant ABS material according to claim 1, characterized in that: The antibacterial agent is selected from at least one of chitosan, nano-tin oxide and nano-silicon dioxide.
5. The antibacterial and aging-resistant ABS material according to claim 1 is characterized in that: The toughening agent is selected from at least one of hydrogenated butadiene / styrene copolymer rubber, hydrogenated styrene / isoprene copolymer rubber, and hydrogenated butadiene / styrene / isoprene copolymer rubber; The number average molecular weight of the toughening agent is 50,000 to 150,000 g / mol; The degree of hydrogenation of the toughening agent is 50-100%.
6. The antibacterial and aging-resistant ABS material according to claim 1, characterized in that: The flame retardant includes at least one of triphenyl phosphate, triisopropylphenyl phosphate, bisphenol A bis(diphenyl phosphate), bisphenol A bis(diisopropylphenyl phosphate), resorcinol bis(diphenyl phosphate), and resorcinol bis(diisopropylphenyl phosphate).
7. The antibacterial and aging-resistant ABS material according to claim 6, characterized in that: The flame retardant also includes fluorinated polyolefin; The fluorinated polyolefin is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, and ethylene / tetrafluoroethylene copolymer; The fluorinated polyolefin accounts for 0.1-10% of the total weight of the flame retardant.
8. The antibacterial and aging-resistant ABS material according to claim 1, characterized in that: The filling aid is selected from at least one of talc, mica, wollastonite, glass microspheres, glass fiber, graphite, carbon fiber, and graphene; The plasticizer is selected from at least one of dibutyl phthalate, dioctyl phthalate and diphenyl phthalate; The antioxidant is selected from at least one of hindered phenols, phosphites, thioesters and derivatives thereof.
9. A method for preparing the antibacterial and aging-resistant ABS material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The ABS substrate, anti-light aging agent, antibacterial agent, toughening agent, flame retardant, filling aid, plasticizer and antioxidant are mixed and then extruded by twin-screw melt processing to obtain the antibacterial and aging-resistant ABS material; The temperature of the twin-screw melt processing is 200-240° C., and the screw speed is 200-800 rpm.
10. Use of the antibacterial and aging-resistant ABS material according to any one of claims 1 to 8, in but not limited to the fields of medical treatment, sanitation, home appliances, and automobiles.
Citation Information
Patent Citations
Preparation method of weather-resistant anti-aging ABS (acrylonitrile-butadiene-styrene) resin
CN103539899A
ABS plastic
CN106928629A
Acrylonitrile-butadiene-styrene copolymer transparent resin having superior chemical resistance and transparency and prepartion thereof
CN1578795A
Improved styrene-acrylonitrile copolymers
GB778265A